Guidelines on the Inclusion of Students of Different Beliefs in Catholic Secondary Schools - Mullally, Aiveen (JMB, 2019)
This second edition of the Inclusion of Students of Different Beliefs in Catholic Secondary Schools arises out of an acknowledgement that the make-up of the Catholic school population in Ireland has continued to change considerably in the past decade. An increasingly diverse population in terms of culture, language and belief systems is enriching our school environments. Simultaneously, a rise in the number of people declaring that they have no religion and an increase in those loosely identifying with their Christian identity are all part of the community that makes up Catholic schools in Ireland. The 2016 census highlights the decline in numbers of people identifying as Roman Catholic in Ireland, falling from 84.2% in 2011 to 78.3% in 2016 (CSO 2017). It also tells us that half the citizens who do not identify as Irish in the 2016 Census are Roman Catholic, namely people from Poland, Lithuania, the Philippines, Nigeria and Brazil. While this growing religious and cultural diversity enriches our school communities, it also poses challenges to schools as they seek to adopt more inclusive practices. Public debates are ongoing on the role of religious education in schools, on religious pluralism, and about what equality in education in Ireland now means. This document seeks to offer practical suggestions for Catholic school communities on how to welcome and accommodate all students, including those of different beliefs and those with no religious affiliation, while remaining true to the characteristic spirit of their school and the Gospel values that motivate Catholic education.